POTENSI PENGEMBANGAN PASAR JAMU - Bagus Wicaksena; Nugroho Ari Subekti (Buletin Ilmiah Litbang Perdagangan, 2010)
Indonesia is a biodiversity country with nine thousand herbs which have the potential as raw materials for traditional medicine, popularly known as Jamu. Jamu is a home industrial product that can be beneficial for economy development through job creation, large number of enterprises of about 90% are small industries, and multiplier-effect created for added value product from upstream to downstream industry. This research shows that the declaration of “Jamu Brand Indonesia” has significant role to build public awareness to consume in which some consumers are to reduce consumption. The reasons due to its low standard in which jamu with chemicals contents, as well as its less competitiveness to import and pharmaceutical products.Nonetheless, most respondents’s perceptions like jamu is “product of Indonesia”, the efficacious supplement product, natural-content based product, and affordable price product must be comprehensively managed by inter-relationship among producer, the government, and academician to rise its competitiveness to pharmaceutical products. This research recomends stipulated policy and selected strategy should be aimed in order to reach 4 M Mode;: Modern, Mutu Tinggi (High Quality), Murah (Affordable), and Memasyarakat (Community Oriented).